Toward Creating a Regional Monetary Arrangement in East Asia - C. Fred Bergsten; Yung Chul Park (Asian Development Bank Institute (ADBI), 2002)
The idea of an Asian Monetary Fund (AMF), which was first raised in 1997, culminated in an agreement among the finance ministers of ASEAN plus PRC, Japan, and Korea (ASEAN+3) to establish a system of swap arrangements among their countries in what is known as the Chiang Mai Initiative (CMI) on May 6, 2000. Policymakers of the ASEAN+3 have made considerable progress over the past three years in increasing the availability of liquidity as they have succeeded in contracting a number of bilateral swaps and establishing informal mechanisms of policy dialogues and reviews among the ASEAN+3. However, the CMI is in an embryonic stage of development, and as such requires a great deal of expansion and consolidation to serve as an efficient regional liquidity support system. This paper analyzes possibilities of, and prospects for, constructing a regional financial arrangement in East Asia by augmenting liquidity support and broadening the scope of cooperation through the CMI. Through an evolutionary process of enlargement and consolidation of the CMI, this study envisions creation of a possible Asian Monetary Fund that is complete with financial support facilities, a monitoring and surveillance mechanism, and a regional collective exchange rate system with a view to adopting a common currency as a long-term objective. A detailed proposal for an operational structure of the CMI is presented. Issues related to surveillance and regional exchange rate policy cooperation are also analyzed.
hdl:11540/4155
Keywords: 330